Neither altered incubation temperature during fetal development nor preferred rearing temperature improves leg bone characteristics of broilers - Morita, Viviane S. [UNESP]; Almeida, Ayla R. [UNESP]; Matos Junior, João B.; Vicentini, Tamiris I. [UNESP]; Zanirato, Gisele L. [UNESP]; Boleli, Isabel C. [UNESP] (Elsevier, 2020)
The present study evaluated whether broiler femoral and tibiotarsal characteristics (as assessed at slaughter age) could be improved if birds were reared under their preferred temperature and whether continuous high or low incubation temperature during the fetal period improves bone characteristics of broilers reared under heat stress or thermal preference. Broiler breeder eggs were incubated from day 13 until hatching under cold (36 °C), control (37.5 °C), or hot (39 °C) temperatures. Under these conditions, the eggshell temperatures were 37.4 ± 0.1°C, 37.8 ± 0.15°C, and 38.8 ± 0.3°C, respectively. Then, broiler chicks were reared under control, preferred (determined previously in thermal preference test), or high temperatures. At day 42 of age, the broilers were weighed and euthanized, and femora and tibiotarsi collected to measure weight, length, diaphysis perimeter, breaking strength, maximum flexion, rigidity, ash, phosphorus, and calcium. Rearing under the preferred temperature did not affect broiler body weight or femoral and tibiotarsal characteristics (P > 0.05). In contrast, high rearing temperature, decreased the body weight, mineral contents of both bones, femoral breaking strength, and tibiotarsal rigidity (P < 0.05). Regarding incubation temperature effects, egg exposure to cold and hot temperatures during the fetal period minimized or avoided a few effects of high rearing temperature, such as those on femoral and tibiotarsal morphological characteristics, mineral composition, and mechanical properties at slaughter age (P < 0.05), but not all. In conclusion, rearing under the preferred broiler temperature did not improve the bone characteristics, and the negative effects of high rearing temperature on bone development were minimized but not completely prevented by high or low temperature incubation during the fetal period.
Keywords: Femur; Heat stress; Incubation temperature; Leg bones; Thermal preference; Tibiotarsus